Do consumers actually sense that sashimi made from frozen-thawed fish tastes worse than non-frozen one?. (March 2020) - Watanabe, Manabu; Suzuki, Toru; Ichimaida, Kiyoyuki; Hattori, Tsukiko; Ueda, Reiko
Highlights: Raw saury meat of frozen-thawed and non-frozen were compared in consumer preference. Consumer panel sensory evaluation by 103 panellists was executed with extreme care. Consumer preference was not significantly varied between frozen and non-frozen. Linguistic information 'frozen' drastically reduced the consumer preference. Influence of the information 'frozen' was inferred based on statistical analysis. Abstract: Freezing preservation is the only technique that has potential to preserve food as it is even for years. It can also bring us important benefits such as; stable food supply, saving energy, reducing environmental load, food loss and parasites risk. However, many consumers are suspected to have prejudice "frozen food does not taste good" that might be the biggest obstacle to the further utilisation of frozen preservation, especially for the fishery food consumed in raw as sushi or sashimi. Therefore, sensory evaluation of sashimi made of Pacific saury was attempted to investigate whether the consumer preference of frozen-thawed fish is apparently worse than non-frozen fish. The influence of linguistic information 'frozen' on the consumer preference was also investigated. Pair test was conducted to compare non-frozen sample and frozen sample. The test was executed twice where 1st test was made without any information and 2nd test was made with disclosing whether the sample was non-frozen or frozen. To execute consumer panel sensory evaluation of sashimi, extremely careful preparations were applied for whole process from harvest to serving to ensure the consistent quality of all pieces of sashimi, by cooperation with a fish supplier and a chef training college. As a result, it was confirmed the average score of the preference was almost same regardless of frozen/non-frozen under the blind condition. However, by disclosing the information frozen/non-frozen, the score for frozen-thawed saury drastically decreased. Factor analysis was further executed to discuss the reason why the information 'frozen' decreased the consumer preferences.